2022
DOI: 10.1002/jmv.28153
|View full text |Cite
|
Sign up to set email alerts
|

Clinical outcomes and economic burden of seasonal influenza and other respiratory virus infections in hospitalized adults

Abstract: The cost of influenza and other respiratory virus infections should be determined to analyze the real burden of these diseases. We aimed to investigate the clinical outcomes and cost of illness due to respiratory virus infections in hospitalized adult patients. Hospitalized patients who had nasal swab sampling for a suspected viral infection between August 1, 2018 to March 31, 2019 were included. Outcome variables were oxygen requirement, mechanical ventilation need, intensive care unit admission, and cost. At… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
1

Year Published

2023
2023
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 39 publications
0
6
1
Order By: Relevance
“…Our results were slightly lower than those of a previous study that reported mean estimated costs of USD8,330 for hospitalised patients aged 65-84 years [11]. Meanwhile, a recent study reported comparable results, with the average cost of hospitalisation per person being USD3,274 in the influenza-positive group, which included adults aged �18 years in the study population [26]. Our results indicated that influenza imposed a substantial annual economic burden.…”
Section: Plos Onecontrasting
confidence: 80%
“…Our results were slightly lower than those of a previous study that reported mean estimated costs of USD8,330 for hospitalised patients aged 65-84 years [11]. Meanwhile, a recent study reported comparable results, with the average cost of hospitalisation per person being USD3,274 in the influenza-positive group, which included adults aged �18 years in the study population [26]. Our results indicated that influenza imposed a substantial annual economic burden.…”
Section: Plos Onecontrasting
confidence: 80%
“…Overall, the average cost (SD) per-inpatient stay was €4,007 (€ 7,620) for all epidemic seasons. Similarly, a recent study [ 49 ] on Turkish population aged > 18 years referring to the epidemic season 2018–2019 showed daily hospital costs equal to 3,274 USD in the influenza-positive group ( N = 55), a higher value than non-influenza patients ( N = 137; 2,765 USD) but also patients admitted with other respiratory infections but not influenza ( N = 70; 3,103 USD). Taken together, our data highlight the significant clinical burden of seasonal influenza mainly on vulnerable individuals, and the high economic impact on the Italian healthcare system.…”
Section: Discussionmentioning
confidence: 77%
“…Viral infections pose a significant economic burden and societal threat worldwide. [1][2][3] The recent COVID-19 pandemic caused by severe acute respiratory syndrome coronavirus 2 (SARS-Co V -2 ) has starkly highlighted the risks posed by respiratory viruses to vulnerable populations and the urgent need for effective antivirals. Respiratory Syncytial Virus (RSV) is also a poten t respiratory pathogen and is responsible for high levels of acut e lower respiratory tract infections in infants, the elderly an d immunocompromi sed adults.…”
Section: Introductionmentioning
confidence: 99%